Evaluation of The Implementation of The Getting Zero To Halinar (Handphone, Pungli, Narkoba) Programm in The Correctional Institutions of The Class I Cipinang Jakarta - Indra Jaya Ali; R. Madhakomala; Corry Yohana (Journal of Business and Behavioural Entrepreneurship, 2019)
The aims of this study is to evaluate the implementation and regulations and legal policies regarding the "Getting Zero To HALINAR" program in The Correctional Institutions (LAPAS) of Class 1 Cipinang Jakarta and the HRM approach are used as treatments to realize zero halinar as one of the conditions required for the implementation of Vision Vision and Correctional Mission The existence of the program has not yet had a positive impact in fostering inmates proven to still be the abuse of the use of mobile phones, extortion and narcotics so that it raises illegal costs (extortion) .This study uses a qualitative approach, a policy evaluation research method. interviews, observations, and literature studies Analysis carried out by following the path determined in the difference evaluation model - DEM The evaluation results of the implementation of the program are relatively effective although they have not yet reached their ideal goals as the Director Circular Correctional Number: PAS-54.PK.01.04.01 of 2013 concerning the program to get zero for halinar. Based on primary data, there were still some problems found in almost every aspect evaluated. Therefore, researchers offer a number of recommendations including increasing integrity by internalizing the contents of the Getting Zero to Halinar program to Officers / Employees / Officers and prisoners in each LAPAS in order to improve HR competencies through education and training, increasing mutual trust in institutions to reduce or eliminate negative excesses from the sectoral egos of each party, strengthening the Employee Internal Control System - SPIP in Cipinang Class IA Laps by ensuring that the working mechanism of the SPIP team at LAPAS runs as it should, and periodic (2 years) evaluation and follow-up evaluation plans .